Investigation of medication adherence and reasons for poor adherence in patients on long-term glaucoma treatment regimes - McClelland JF; Bodle L; Little JA (Patient Preference and Adherence, 2019)
Julie F McClelland,1 Lynne Bodle,1,2 Julie-Anne Little11Vision Science Research Group, Biomedical Sciences Research Institute, Ulster University, Coleraine, UK; 2Department of Ophthalmology, Flinders Medical Centre, Flinders University, Adelaide, SA, AustraliaPurpose: Long-term treatment adherence for a chronic asymptomatic condition is a demanding task for many patients. Treating progressive glaucoma can also be confounding for physicians, particularly when management relies on assumption of adherence. This study investigated associations between self-reported adherence and frequency of medication changes due to glaucoma progression.Methods: A total of 128 participants with primary open angle glaucoma were recruited from glaucoma clinics in Flinders Eye Center, South Australia, and completed confidential questionnaires. Information was obtained regarding beliefs about glaucoma and their treatment. Adherence was assessed using the four-item Morisky, Green and Levine Medication Adherence Questionnaire (MGL). Medical records were analyzed for the number of medication changes, due to glaucoma progression.Results: Adherence to topical glaucoma medication was categorized as ‘high’ in 41.4% (Morisky, Green and Levine (MGL). Data were analyzed for behaviors affecting adherence, history of adherence, and reasons for changed adherence. Chi-squared test demonstrated that there was no significant association noted between adherence and changes in medication regime (χ2 (2,128)=0.968, P=0.915); however, a significantly lower adherence was detected if participants had difficulties with their drop regime (χ2 (2,128)=7.24, P=0.027) or had help with drop insertion (χ2 (1,128)=9.77, P=0.008).Conclusion: This study revealed a higher rate of non-adherence than has previously been demonstrated in other studies. This may be attributed to the unique design of the confidential questionnaire and the independent and sympathetic questioning techniques used. Further work to develop a specific glaucoma medication adherence questionnaire would be valuable to enhance glaucoma management.Keywords: glaucoma, compliance, adherence, topical medication, questionnaire